Hubungan Asupan Lemak terhadap Kualitas Tidur pada Lansia di Wilayah Pesisir Kecamatan Tuban - Icha Atmasari; Tysa Runingsari (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is one of the most common health problems among the elderly and has the potential to cause serious complications such as heart disease and stroke. Dietary patterns and lifestyle factors are known to play an important role in increasing blood pressure, particularly fat intake and sleep quality. This study aimed to analyze the relationship between fat intake and sleep quality with the incidence of hypertension among elderly individuals in the coastal area of Tuban District. This study used an analytical observational design with a case-control approach. The total number of respondents in this study was 136 elderly individuals, consisting of 68 cases (elderly with hypertension) and 68 controls (elderly without hypertension). Data on fat intake were obtained using a 24-hour food recall method, while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed using the Pearson Chi-Square test with a significance level of α ≤ 0.05. The results showed that there were significant relationships between fat intake (p = 0.000) and sleep quality (p = 0.000) with the incidence of hypertension among the elderly in the coastal area of Tuban District. Elderly individuals with high fat intake and poor sleep quality were more frequently found in the hypertension group compared to the non-hypertension group. In conclusion, fat intake and sleep quality are associated with the occurrence of hypertension among the elderly. Hypertension control efforts can be carried out through limiting fat intake and maintaining good sleep quality.